Comment on 'Monogamy of multi-qubit entanglement using Rényi entropy'. (30th January 2018) - Yu, Long-Bao; Zhang, Li-Hua; Zhao, Jun-Long; Tang, Yong-Sheng
Abstract: In an article in 2010, Kim et al introduced the definition of Rényi- α entanglement for bipartite quantum states and established an analytic formula of Rényi- α entanglement for arbitrary two-qubit states with α ⩾ 1 . They also derived a monogamy of entanglement in multi-qubit systems in terms of Rényi- α entanglement for α ⩾ 2 Kim et al (2010 J. Phys. A: Math. Theor .43 445305). We find the proofs of theorems 2 and 3 contain some errors and we also present an improved derivation to overcome this flaw. The alternative derivation shows that the main conclusions remain valid despite the invalidity of the proofs.